Assessment of high fluoride in water sources and endemic fluorosis in the North-Eastern communities of Gombe State, Nigeria. Issue 1 (1st January 2021) - Giwa, Abdulmoseen Segun; Memon, Abdul Ghaffar; Ahmad, Jabran; Ismail, Tariq; Abbasi, Sikandar Ali; Kamran, Kashif; Wang, Baozhen; Segun, Bamidele; Seydou, Hankouraou
ABSTRACT: Fluoride content of drinking water sources in 12 communities in North-Eastern states, Nigeria, was investigation. The fluoride concentration analyses were performed using the SPADNS method according to the standard method for examining water and wastewater. Fluoride concentration was in the range of 0.35–3.46 mg/L in the drinking water sources. Notably, communities with high fluoride content above the World Health Organization (WHO) guideline were observed in Tumu-2 (2.88 mg/L), Lapan (3.46 mg/L), Jalingo (1.79 mg/L), and Kaleh (1.60 mg/L), respectively. The physical survey conducted indicates severe affliction of fluorosis in Lapan communities; (38% dental fluorosis, 27% skeletal fluorosis, 22% dental and skeletal, 13% without fluorosis), thus, demanding to be urgently redressed. Different water de-fluoridation processes, technologies selection, limitations, and strengths that could serve as treatment purposes in diverse conditions were proposed and highlighted to aid relevant authorities in the future implementation of mitigation measures.